2008
DOI: 10.1111/j.1545-5300.2008.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared Ancestry, Evolving Stories: Similar and Contrasting Life Experiences Described by Foreign Born and U.S. Born Latino Parents

Abstract: As the Latino population in the United States continues to increase, so does the necessity for in-depth knowledge about their life experiences. This qualitative study sought to privilege the voices of Latino parents by utilizing focus group discussions. Specifically, participants described the life experiences that have the greatest influence on their parenting efforts. Similar and contrasting themes were identified based on participant country of origin (i.e., foreign born vs. U.S. born). Findings described t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 25 publications
4
75
0
Order By: Relevance
“…First, our findings are consistent with studies that show more collectivist and complex care structures among Latinos and across Latin America, although there are clear differences among countries, across social classes, between women and men, and across immigrant generations (Sotomayor 1992, Vega 1995, Delgado and Tennstedt 1997a,b, Wilmoth 2001, Beyene et al 2002, Pelaez and Martinez 2002, Aranda 2003, Pelaez 2005, Parra-Cardona et al 2008. There is substantial empirical evidence that these similar care structures and networks are rooted in common cultural values of familism, respect for older adults, and social and moral obligations to support and care for family members, especially older and ill parents (Cox and Monk 1993, Cortes 1995, Clark and Huttlinger 1998, Montoro Rodriguez and Kosloski 1998, Lugo Steidel and Contreras 2003, Ramos 2004, Neary and Mahoney 2005, Borrayo et al 2007, Kao et al 2007, Parra-Cardona et al 2008, Wells et al 2008. Although Puerto Ricans are US citizens, Puerto Rican culture and geographic mobility mirror that of Latino immigrants to the USA.…”
Section: Resultssupporting
confidence: 91%
“…First, our findings are consistent with studies that show more collectivist and complex care structures among Latinos and across Latin America, although there are clear differences among countries, across social classes, between women and men, and across immigrant generations (Sotomayor 1992, Vega 1995, Delgado and Tennstedt 1997a,b, Wilmoth 2001, Beyene et al 2002, Pelaez and Martinez 2002, Aranda 2003, Pelaez 2005, Parra-Cardona et al 2008. There is substantial empirical evidence that these similar care structures and networks are rooted in common cultural values of familism, respect for older adults, and social and moral obligations to support and care for family members, especially older and ill parents (Cox and Monk 1993, Cortes 1995, Clark and Huttlinger 1998, Montoro Rodriguez and Kosloski 1998, Lugo Steidel and Contreras 2003, Ramos 2004, Neary and Mahoney 2005, Borrayo et al 2007, Kao et al 2007, Parra-Cardona et al 2008, Wells et al 2008. Although Puerto Ricans are US citizens, Puerto Rican culture and geographic mobility mirror that of Latino immigrants to the USA.…”
Section: Resultssupporting
confidence: 91%
“…These investigators indicated that more acculturated persons attempt to find support in extended family and friends, whereas those who are less acculturated tend to rely on the nuclear family (Parra-Cordova, Cordova, Holtrop, Villaruel, & Wieling, 2008;Skogrand, Hatch, & Singh, 2005). In addition, Griffith and Villavicencio (1985) determined that the use of extended family and friends for support is positively associated with education and financial income.…”
Section: Discussionmentioning
confidence: 96%
“…Successful completion of this study was therefore only possible because of the commitment, leadership, and guidance provided by the community partners. In particular, the support of community partners was critical given the diverse ways in which the current antiimmigration climate in the United States has negatively impacted the lives of participants from both sites (Parra Cardona, Córdova, Holtrop, Villarruel, et al 2008). Many participants were concerned about becoming involved in a focus group because they did not initially trust that their confidentiality would be protected.…”
Section: Methodsmentioning
confidence: 99%